"Is it beneficial to stress grades to my child?" - Relationships between parental attitudes towards academic achievement, motivation, academic self-concept and academic achievement in adolescents - Peixoto, Francisco (2011)
In this study we analyse the relations of parental attitudes towards academic achievement (process-centred vs. performance-centred) with self-representations, motivational orientations and academic achievement. Participants were 498 students attending 7th and 9th grades. To collect data we used a self-concept scale (Peixoto & Almeida, 1999), a scale of motivational orientations (Skaalvik, 1997), and a scale to assess parental attitudes towards academic performance (Antunes & Fontaine, 2003). Correlation analysis showed positive associations between processes centred attitudes and academic self-concept, self-esteem, task orientation, and academic achievement. Performance centred attitudes were negatively correlated with academic self-concept, self-esteem and academic achievement, and positively related to selfenhancing ego orientation, self-defeating ego orientation and avoidance orientation. Structural equation modelling revealed different paths, in the relationship between parental attitudes and academic achievement, for process centred attitudes and for performance centred attitudes. Results in this study support the idea that the perception of parental attitudes centred in the process are related to positive outcomes while parental attitudes centred on performance are related to less positive outcomes. Finally, data in this study converges with the existing literature that highlights the mediating role of individual characteristics such as self-concept and motivational orientations in the relationship between parental attitudes and academic achievement.